Regrowth of microorganisms from treatment to tap in operational drinking water supply networks - Carneiro, Isabel; Fish, Katherine; Jarvis, Peter; Haley, John A.; Webber, Fiona; Gaskin, Paul; Boxall, Joby (MDPI, 2024)
This research provides new understanding of the (re)growth of microorganisms within drinking water distribution networks. Flow cytometry data quantifying total and intact cell counts from consumers’ taps are currently rare, and its value for aiding understanding of the growth of microorganisms is unknown. In this study, changes in microbial concentrations from the treatment works to customers’ taps were measured (using flow cytometry) in two UK drinking water distribution networks. Throughout each network, five locations were sampled for five consecutive days within a week, and to assess seasonal impacts, this was repeated twice in each network. Significant growth of microorganisms was observed in both networks during autumn, particularly at higher-water-age taps. These results give novel emphasis to the active impact of the distribution system on microbiological growth by using flow cytometry data collected in a systematic way from treatment through to customers’ taps. Such understanding is essential to achieving the delivery of safe and aesthetically pleasing drinking water to customers.
The 3rd International Joint Conference on Water Distribution Systems Analysis & Computing and Control for the Water Industry (WDSA/CCWI 2024). 1-4 July 2024, Ferrara, Italy